Serotonergic mechanisms on breathing modulation in the rat locus coeruleus - Moreno, Vanessa de Souza [UNESP]; Bicego, Kenia C. [UNESP]; Szawka, Raphael E.; Anselmo-Franci, Janete A.; Gargaglioni, Luciane H. [UNESP] (Springer, 2010)
The locus coeruleus (LC) is a noradrenergic nucleus that plays an important role in the ventilatory response to hypercapnia. This nucleus is densely innervated by serotonergic fibers and contains high density of serotonin (5-HT) receptors, including 5-HT(1A) and 5-HT(2). We assessed the possible modulation of respiratory response to hypercapnia by 5-HT, through 5-HT(1A) and 5-HT(2) receptors, in the LC. To this end, we determined the concentrations of 5-HT and its metabolite 5-hydroxyindole-3-acetic acid (5-HIAA) in the LC after hypercapnic exposure. Pulmonary ventilation (V(E), plethysmograph) was measured before and after unilateral microinjection (100 nL) of WAY-100635 (5-HT(1A) antagonist, 5.6 and 56 mM), 8-OHDPAT (5-HT(1A/7) agonist, 7 and 15 mM), Ketanserin (5-HT(2A) antagonist, 3.7 and 37 mM), or (+/-)-2,5-dimethoxy-4-iodoamphetaminehydrochloride (DOI; 5-HT(2A) agonist, 6.7 and 67 mM) into the LC, followed by a 60-min period of 7% CO(2) exposure. Hypercapnia increased 5-HTIAA levels and 5-HIAA/5-HT ratio within the LC. WAY-100635 and 8-OHDPAT intra-LC decreased the hypercapnic ventilatory response due to a lower tidal volume. Ketanserin increased CO(2) drive to breathing and DOI caused the opposite response, both acting on tidal volume. The current results provide evidence of increased 5-HT release during hypercapnia in the LC and that 5-HT presents an inhibitory modulation of the stimulatory role of LC on hypercapnic ventilatory response, acting through postsynaptic 5-HT(2A) receptors in this nucleus. In addition, hypercapnic responses seem to be also regulated by presynaptic 5-HT(1A) receptors in the LC.
Keywords: Chemosensitivity; A6 region; Hypercapnia; Ventilation; Pons; Serotonin; 5-HT(1A); 5HT(2A)